La oralidad: un análisis de los procesos pedagógicos implementados durante la educación básica primaria y secundaria (2016)
The written language has overshadowed the process of teaching of the orality, leaving aside the social and educational need to acquire oral communication skills. This reality has caused that, over time, orality occupy a place relegated regarding writing in the education system and that teachers lack teaching tools and strategies for teaching.